The Effectiveness of Emergency Response System’s Service Providers for Road Accidents in Johor Bahru, Malaysia - Mustaffa, A.A.; Kazunori, H. (Civil Engineering Dimension, 2012)
In Malaysia, there are three core services involved in emergency, namely the fire and rescue, police, and ambulance services. The aim of the service providers is to prevent the loss of life and damage by improving their response time. The Civil Defence Department and the 999 call centre also assist the main providers. This paper aims to provide an overview of emergency response system (ERS) for road accidents in Johor Bahru. The objective is to find the effective services from ERS works. There are three sections of chronological events involved: the call centre receiving reports on accidents, at location of the accident and the time during which the victims are brought to the hospital. The paper studies the operation scheme of the ERS by describing the condition; to analyse the questionnaire using a set of questions on the ERS service; and to determine the effectiveness of the services provided. The provider’s services can be identified as a main factor in improving the ERS services provided in the study area.